ISLAMIC PHILANTHROPY AND COMMUNITY SOLIDARITY AMONG CHINESE MUSLIMS IN SOUTH SUMATRA - Dian Pertiwi; Maya Panorama; Rika Lidyah (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to determine how Islamic philanthropy strengthens social solidarity within the Chinese Muslim community in South Sumatra through zakat, infaq, sedekah, waqf and social donations, as well as charitable programs, religious study groups (Majelis Taklim), guidance for converts to Islam, and religious activities during Ramadan. This study used a qualitative case study approach that included observation, in-depth interviews, and documentation of philanthropic activities. Four informants participated: two representatives from PITI and two community members. Additionally, activity records, news stories, and publication pertinent to PITI South Sumatra’s charitable endeavors were used to gather research data. Field data collection lasted three months. Thematically, the data were analyzed through transcription, coding, theme categorization, and interpretation to examine the relationship between philanthropic activities and strengthening social solidarity. Islamic philanthropy increases member participation, builds trust, norms of reciprocity, and community cohesion. Transparent fund distribution and socio-religious programs strengthen internal solidarity, while collaboration with donors and external institutions expands social networks and enhances community legitimacy. These results demonstrate the importance of governance and collaboration in philanthropy to build solidarity. The study is limited to one community and is qualitative in nature, so the results cannot be generalized, and the economic impact was not analyzed. This research provides empirical evidence regarding the role of Islamic philanthropy in building solidarity among minority communities and serves as a reference for more effective management of socio-religious for quantitative and comparative research in other communities.